The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1001/jamaoncol.2014.216
|View full text |Cite|
|
Sign up to set email alerts
|

Comprehensive Genomic Profiling of Carcinoma of Unknown Primary Site

Abstract: Almost all CUP samples harbored at least 1 clinically relevant GA with potential to influence and personalize therapy. The ACUP tumors were more frequently driven by GAs in the highly druggable RTK/Ras/mitogen-activated protein kinase (MAPK) signaling pathway than the non-ACUP tumors. Comprehensive genomic profiling can identify novel treatment paradigms to address the limited options and poor prognoses of patients with CUP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
216
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(252 citation statements)
references
References 56 publications
22
216
0
8
Order By: Relevance
“…The most frequent alterations were in the TP53 gene; these alterations were detected in 37.1% of cases, followed by aberrations in KRAS (18.6%), and PIK3CA (15.4%). These results are consistent with previous reports of approximate frequencies of gene alterations in tissue samples from CUP patients (15,16) (Supplemental Figure 6). …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The most frequent alterations were in the TP53 gene; these alterations were detected in 37.1% of cases, followed by aberrations in KRAS (18.6%), and PIK3CA (15.4%). These results are consistent with previous reports of approximate frequencies of gene alterations in tissue samples from CUP patients (15,16) (Supplemental Figure 6). …”
Section: Discussionsupporting
confidence: 93%
“…Further understanding of the underlying genomic alterations among patients with CUP may also prove useful. Previous studies using archival tumor tissues of CUP patients found that TP53 (38–55%), KRAS (18–20%), CDKN2A (19%), MYC (12%), ARID1A (11%) and PIK3CA (9–14%) were frequently altered as assessed by targeted next-generation sequencing (NGS) (15,16). Although genomic sequencing is generally done on archival cancer samples, limitations with the use of tissues include intra-tumor genomic heterogeneity (17) as well as the dynamic mutational processes that can occur along with therapeutic intervention (18).…”
Section: Introductionmentioning
confidence: 99%
“…Recent comprehensive genomic profiling of 200 CUP specimens revealed targetable genetic alterations presented in 96% of patients 9. The authors furthermore described two patients for whom targeted therapies selected on the basis of the tumour genomic profile—a MET amplification and EML4-ALK fusion, respectively—led to sustained complete responses on crizotinib.…”
Section: Discussionmentioning
confidence: 99%
“…• Carcinoma escamocelular metastásico de cuello que frecuentemente se manifiesta con adenopatía cervical (2) HER2 (1, 2) EGFR, (2,21) C kit (1) PDGFR (1) BCL2 (2,8) KRAS (22) p53 (1,8,23) c-Met (1,24) pMAPK (25) Notch 3 (25), PTEN (22,25) pAKT, pRPS6 (25), p21 (25) TIMP-1,(2, 10), MMP2, 9 (1, 2, 10) E-cadherina (25) EMT (25) kiSS1 (2) VEGF (1, 2, 8, 10)…”
Section: Clasificaciónmentioning
confidence: 99%